Does Asymmetrical Gonopodium Morphology Predict Lateralized Behavior in the Fish Xenophallus umbratilis? - Johnson, Erik S.; Nielsen, Mary-Elise; Johnson, Jerald B. (Frontiers in Ecology and Evolution, 2020)
Why bilaterally symmetrical organisms express handedness remains an important question in evolutionary biology. In some species, anatomical asymmetries have evolved that accompany behavioral handedness, yet we know remarkably little about causal links between asymmetric morphological traits and behavior. Here, we explore if a dextral or sinistral orientation of the male intromittent organ predicts side preferences in male behaviors. Our study addresses this question in the Costa Rican livebearing fish, Xenophallus umbratilis. This fish has a bilaterally symmetrical body plan, with one exception—the male anal fin (gonopodium), used to inseminate females, terminates with a distinct left- or right-handed corkscrew morphology. We used a detour assay to test males for side biases in approach behavior when exposed to four different stimuli (predator, potential mate, novel object, empty tank control). We found that left morph males preferred using their right eye to view potential mates, predators, and the control, and that right morph males preferred to use their left eye to view potential mates and predators, and their right eye to view the control. Males of both morphs displayed no eye bias when approaching the novel object. Our results suggest that there is a strong link between behavior and gonopodium orientation, with right and left morph males responding with opposite directional behaviors when presented with the same stimuli. This presents the intriguing possibility that mating preferences—in this case constrained by gonopodial morphology—could be driving lateralized decision making in a variety of non-mating behaviors.